Answer :
Answer:
[tex]x=1\\x=-1[/tex]
Step-by-step explanation:
[tex]9x^{4} -2x^{2} -7=0\\y=x^{2} \\9y^{2} -2y-7=0\\y=\frac{2\pm\sqrt{(-2)^{2} -4*9(-7)} }{2*9} =\frac{2\pm\sqrt{4+252} }{18} =\frac{2\pm\sqrt{256} }{18}[/tex]
[tex]\sqrt{256} =16[/tex]
[tex]y=\frac{2+16}{18} =\frac{18}{18} =1 \\or \\y=\frac{2-16}{18} =-\frac{14}{18} =-\frac{7}{9}[/tex]
[tex]x^{2} = 1 \\or \\x^{2} =-\frac{7}{9}[/tex]
[tex]x=\pm 1[/tex]
[tex]x^{2} =-\frac{7}{9}[/tex] has no solution since fot all [tex]x[/tex] on the real line, [tex]x^{2} \geq 0[/tex] and [tex]-\frac{7}{9} < 0.[/tex]